PERSONAL HIGIENE UNTUK MENCEGAH KECACINGAN DI SD INPRES BUKIT KEL. TAMARUNANG KEC. SOMBA OPU GOWA - Dewi Arisanti; Anita Anita; Rahmawati Rahmawati; Mujahidah Basarang (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
Efforts to prevent worms include maintaining good body hygiene, good environmental hygiene, good and clean food and drink, wearing footwear, defecating in the toilet, maintaining good personal hygiene such as cutting nails and washing hands before eating. The skin is the place where germs enter the body, loose soil (sand, humus) is good soil for the growth of worm larvae. Cleaning long and dirty fingernails causes accumulation of dirt and disease germs. Clean snacks are part of the daily life of almost all age groups and social classes, including elementary school-age children. The purpose of personal hygiene is to improve one's health status and maintain one's personal hygiene. Service activities regarding helminthiasis need to be carried out repeatedly because students can find out how someone can be infected with worms and with infection with worms various health problems can appear and one of them is related to growth in children. Hygiene behavior and maintaining great health need to be given since the child is small, so that it becomes a good habit in the future.